Biology of Chagas disease vectors: biological cycle and emergence rates of Rhodnius marabaensis Souza et al., 2016 (Hemiptera, Reduviidae, Triatominae) under laboratory conditions - Olaia, Nicoly [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP]; de Oliveira, Jader [UNESP]; Cacini, Gustavo Lázari [UNESP]; Souza, Eder dos Santos [UNESP]; Pinotti, Heloisa [UNESP]; da Silva, Lucas Abrantes [UNESP]; da Rosa, João Aristeu [UNESP] (Springer Nature, 2021)
In Latin America, Chagas disease has been mostly transmitted to humans by contact with the feces or urine of triatomine species infected with the protozoan Trypanosoma cruzi. There are currently 156 species in the subfamily Triatominae, distributed in 18 genera and five tribes. The prolixus group of the genus Rhodnius is composed of 11 species. Rhodnius marabaensis was the last species described and considered in this grouping of vectors. Knowledge about the biology, ecology, and behavior of these vectors is of great epidemiological importance, and in order to expand the knowledge of the biology of R. marabaensis, this paper describes the biological cycle and emergence rates of the species under laboratory conditions. The experiment was carried out at temperatures ranging from 15.5 to 29 °C (average of 24 °C) and humidity ranging from 51.4 to 72.2 (average of 63). For each of the fifteen couples, the egg emergence rate was calculated throughout the oviposition period. The oviposition period lasted from February to September, and the emergence rate varied between 13.9 and 53.3%. R. marabaensis presented an emergence rate of 46.7% and a total biological cycle of 193 days (the mean time required for emergence (25.1 days), 1st nymphal instar (19.4 days), 2nd nymphal instar (22.1 days), 3rd nymphal instar (26.2 days), 4th nymphal instar (29.3 days), and 5th nymphal instar (70.9 days)). Based on the biological cycle of R. marabaensis and 14 other Rhodnius species already described in the literature, it was also possible to calculate the averages for the groups prolixus, pictipes, and pallescens and, mainly, for the genus Rhodnius, contributing to the knowledge of this important group of Chagas disease vectors.
Keywords: Chagas disease; Life cycle; Reproductive cycle; Rhodniini; Triatomines